2001
DOI: 10.1099/0022-1317-82-3-655
|View full text |Cite
|
Sign up to set email alerts
|

Recombination, pseudorecombination and synergism of geminiviruses are determinant keys to the epidemic of severe cassava mosaic disease in Uganda

Abstract: The molecular variability of cassava geminiviruses occurring in Uganda was investigated in this study. Infected cassava plants and whiteflies were collected from cassava plantings in different geographical areas of the country and PCR was used for molecular characterization of the viruses. Two complete sequences of DNA-A and -B from African cassava mosaic virus (ACMV), two DNA-A sequences from East African cassava mosaic virus (EACMV), two DNA-B sequences of EACMV and the partial DNA-A nucleotide sequence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
179
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 322 publications
(188 citation statements)
references
References 28 publications
8
179
0
1
Order By: Relevance
“…Synergism between isolates of two cassava-infecting geminiviruses, ACMV and EACMV, has been observed and the genes mediating synergism have been identified (Fondong et al, 2000;Pita et al, 2001;Vanitharani et al, 2004). Synergism between ACMV and East African cassava mosaic Cameroon virus (EACMCV) is a two-way process, as the presence of the DNA-A component of ACMV or EACMCV enhanced the accumulation of viral DNA of EACMCV and ACMV, respectively, in tobacco BY2 protoplasts (Vanitharani et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synergism between isolates of two cassava-infecting geminiviruses, ACMV and EACMV, has been observed and the genes mediating synergism have been identified (Fondong et al, 2000;Pita et al, 2001;Vanitharani et al, 2004). Synergism between ACMV and East African cassava mosaic Cameroon virus (EACMCV) is a two-way process, as the presence of the DNA-A component of ACMV or EACMCV enhanced the accumulation of viral DNA of EACMCV and ACMV, respectively, in tobacco BY2 protoplasts (Vanitharani et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Harrison et al (1997) suggested the possibility of synergism between isolates of the two cassava begomovirus species, African cassava mosaic virus and East African cassava mosaic virus. Molecular evidence for synergism between the cassava-infecting begomoviruses African cassava mosaic virus from Cameroon (ACMV- [CM:98]) and East African cassava mosaic virus from Cameroon (EACMV- [CM:98]) has been demonstrated (Fondong et al, 2000;Pita et al, 2001;Vanitharani et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that recombination plays an important role in the generation of genetic variability in begomoviruses in Brazil (Galvão et al, 2003;Inoue-Nagata et al, 2006;Ribeiro et al, 2007;Silva et al, 2011a,b) and worldwide (Pita et al, 2001;Monci et al, 2002;García-Andrés et al, 2006, 2007a. Recombination analysis showed the occurrence of inter-and intraspecific recombination events in the Rep, CP and CR of the viral isolates detected in Sida spp.…”
Section: Discussionmentioning
confidence: 99%
“…New, highly virulent, strains of African cassava mosaic virus ravage a critical African staple in an epidemic that is still expanding (Legg and Thresh, 2000). These new strains, which can overcome previously resistant lines of cassava, have emerged by recombination between viruses naturally co-existing in cassava (Pita et al, 2001;Zhou et al, 1997). In addition, mutation and recombination of viruses in the laboratory have generated offspring viruses with more severe pathology (Ding et al, 1996).…”
Section: Hgt From Gm Plants To Virusesmentioning
confidence: 99%